CNSS Chair's Select Abstract Presentations: Developmental phosphoproteomics identifies Casein Kinase 2 as a therapeutic target in medulloblastoma. (3rd June 2015) - Purzner, T; Purzner, J; Cho, Y; Elias, J; Scott, M
Abstract : Background: The hedgehog pathway (Hh) is an important developmental signaling pathway that is commonly dysregulated in brain tumors, most notably in medulloblastomas. To identify novel therapeutic targets within the Hh pathway, we performed the first quantitative proteome-wide evaluation of phosphorylation events resulting from in vitro SHH administration and occurring throughout Hh-driven cerebellar development in vivo. Methods: Multiplexed quantitative mass spectrometry was done using Tandem Mass Tags 10-plex reagents, TiO2 phosphopeptide enrichment and HPLC-MS/MS/MS. Results: Motif analysis of 2-fold changing phosphorylation events suggested casein kinase 2 (CK2) was responsible for mediating 45% of all changes in phosphorylation. Epistasis studies revealed that CK2 activity is necessary for hedgehog signaling and affects terminal signaling components, thereby circumventing challenges of emergence of resistance and a priori resistance that are commonly encountered with existing small molecule inhibitors in medulloblastoma. In vivo, mice harboring MB allografts resistant to current therapies showed near-complete cessation of tumor growth in response to a CK2 inhibitor. Conclusion: Our use of developmental phosphoproteomics revealed casein kinase 2 as a key regulator of hedgehog signaling and therapeutic target in medulloblastoma. Our success establishes a foundation for us, and others, to apply a similar approach in different tumor initiating pathways.